2013
DOI: 10.1186/1748-717x-8-89
|View full text |Cite
|
Sign up to set email alerts
|

A comparative dosimetric study for treating left-sided breast cancer for small breast size using five different radiotherapy techniques: conventional tangential field, filed-in-filed, Tangential-IMRT, Multi-beam IMRT and VMAT

Abstract: Background and purposesTo compare the dosimetry for the left-sided breast cancer treatment using five different radiotherapy techniques.Materials and methodsTwenty patients with left sided breast cancer were treated with conservative surgery followed by radiotherapy. They were planned using five different radiotherapy techniques, including: 1) conventional tangential wedge-based fields (TW); 2) field-in-field (FIF) technique; 3) tangential inverse planning intensity-modulated radiation therapy (T-IMRT); 4) mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 22 publications
10
98
1
1
Order By: Relevance
“…The following values were determined for group b: 3D-CRT, 1.5 ± 0.9 Gy; hybrid, 1.1 ± 0.6 Gy (p < 0.01). There is on average 1 Gy less load on the heart for left-sided tumors 3D-CRT three-dimensional conformal radiotherapy, PTV planning target volume, SIB simultaneous integrated boost, HI homogeneity index, CI conformity index Jin et al argued against the use of only VMAT for radiation of left-sided mammary carcinoma because of the high volume that is exposed to low dose and the comparably high dose of the contralateral breast and lung [6]. Moreover, Badakhshi et al could not find an advantage of the sole use of VMAT for the treatment of breast cancer when compared with 3D-CRT and IMRT [7].…”
Section: Resultsmentioning
confidence: 99%
“…The following values were determined for group b: 3D-CRT, 1.5 ± 0.9 Gy; hybrid, 1.1 ± 0.6 Gy (p < 0.01). There is on average 1 Gy less load on the heart for left-sided tumors 3D-CRT three-dimensional conformal radiotherapy, PTV planning target volume, SIB simultaneous integrated boost, HI homogeneity index, CI conformity index Jin et al argued against the use of only VMAT for radiation of left-sided mammary carcinoma because of the high volume that is exposed to low dose and the comparably high dose of the contralateral breast and lung [6]. Moreover, Badakhshi et al could not find an advantage of the sole use of VMAT for the treatment of breast cancer when compared with 3D-CRT and IMRT [7].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the context of whole breast radiotherapy alone, Jin et al [21] reported values for the volume of heart receiving 20 Gy or more (V 20Gy ) of 5.6% for standard tangential wedged fields, 4.3% for forward-planned IMRT, 2.1% for seven-field IMRT and 2.0% for tangential inverseplanned IMRT, suggesting a benefit from the inverseplanned approaches. However, the more complex the field arrangement, the larger the low-dose bath of radiation, such that the mean heart dose may actually be increased by multifield IMRT approaches.…”
Section: Intensity-modulated and Arc Radiotherapy Techniquesmentioning
confidence: 97%
“…Also, VMAT plan had advantages in reducing the volume of high dose with increased volume of lower dose (22)., G. Yavas et al, reported that the monitor units required for the FIF 1950 technique were lower when compared to CRT technique (7). In field in field strategy, the monitor units were adjusted among the sub-fields and even an increase in the number of sub-fields wouldn't have much change in the MUs.…”
Section: Discussion:-mentioning
confidence: 99%